Securitização, representação e racismo: o papel da mídia na percepção do véu islâmico na França - Maia, Beatriz Fonseca da Costa (2025)
This research aims to analyze the impacts of global communication media — with a greater focus on the role of the press — in securitization processes, in order to better understand their effects in terms of public opinion, relevant agendas, and changes in security policies. Thus, the analysis seeks to draw on reflections proposed by scholars in the fields of media and security — especially theorists from the Copenhagen and Paris Schools — to assess the possible influence of the media in the securitization process. In other words, the guiding question of his study is: How does the French media, by conveying racist perceptions, influence the securitization process of the Islamic veil and contribute to the public construction of the notion of threat? To address this topic, a literature review will be conducted on securitization theory and its connections with the media, in order to understand the influence of media outlets in he securitization of the veil. Subsequently, a case study will be carried out through an analysis based on Gilboa’s communication theory, focusing on the newspapers Le Figaro and Le Journal du Dimanche (JDD) during the period from 2009 to 2010 — since this period marks a tightening of French legislation regarding the Islamic veil (Mielniczuk, 2018). The study will examine the securitization of the veil in France by investigating the role that the media played in the process, particularly through the dissemination of discourses that contributed to framing the issue as one of national security and identity